PENGEMBANGAN BAHAN AJAR BERBENTUK POSTER PADA PEMBELAJARAN MATEMATIKA BANGUN DATAR SISWA KELAS IV SEKOLAH DASAR - Annisa Arnun (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to develop teaching materials in the form of posters in learning mathematics flat shapes for grade IV students in elementary schools. This poster teaching material is also validated by material and design experts, then tested in practice and effectiveness. The study was conducted at SD Swasta Arisa Medan Deli with a study subject of 10 fourth grade students. This study used the development model by Thiagarajan and Sammel (1974), which has four stages: define, design, development, and dissemination. The instruments used in this study are material validation questionnaires, designs, practitioners, student responses, and pretest-posttest questions to determine the effectiveness of poster teaching materials. The results of the study explained that the poster teaching materials had gone through the assessment stage by material experts, design experts, practitioners, and field trials. The overall assessment average gets a final score of 90% with a very feasible category. In line with the results of the assessment, the teaching materials in the form of posters that have been developed are suitable for use.